THIN BED IDENTIFICATION IMPROVEMENT USING SHORT – TIME FOURIER TRANSFORM HALF – CEPSTRUM ON “TG” FIELD - Intan Andriani Putri; Awali Priyono (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
Thin Bed Identification is still a difficult task even with the advanced technology of seismic acquisition. Certain high frequency component is necessary and could be obtained through resolution enhancement. Short – Time Fourier Transform Half Cepstrum (STFTHC) is performed to enhance seismic resolution thus a better separation of thin bed could be improved. Basic principal of STFTHC is to replace the frequency spectrum by its logarithm while phase spectrum remains the same. Synthetic seismic was built based on Ricker and Rayleigh criterion. They were used to test the program yielding a better separation of two interfaces under tuning thickness without creating new artifacts. The algorithm was applied to seismic data from TG field. Using post-STFTHC seismic data as input of acoustic impedance inversion, well tie correlation increases by 10% and decreases inversion analysis error by 17,5%. Several thin bed -which once could not- could be identified on acoustic impedance result.